2016
DOI: 10.1136/bjophthalmol-2015-308067
|View full text |Cite
|
Sign up to set email alerts
|

The ophthalmic presentation of Hermansky–Pudlak syndrome 6

Abstract: The diagnosis of HPS in all patients was delayed due to a mild systemic phenotype. Next-generation sequencing can aid diagnosis of syndromic conditions with important consequences for preventing morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(23 reference statements)
1
9
0
1
Order By: Relevance
“…With the recent rapid evolution of affordable next‐generation sequencing methods, there is increased recognition of HPS subjects and new HPS genetic subtypes (Arcot Sadagopan et al, 2017; Wei et al, 2016; Yousaf et al, 2016). This is also evidenced by the increased diagnosis of subjects with nonclassic HPS phenotypes (i.e., HPS‐2, HPS‐7, HPS‐8, HPS‐9, and HPS‐10; Ammann et al, 2016; Bryan et al, 2017; Cetica et al, 2015; Iwata et al, 2017; Okamura et al, 2018), as well as diagnosis of “unexpected” HPS in cohorts with albinism (S. Ito et al, 2005; Khan et al, 2016), immunodeficiency (Badolato et al, 2012), ocular disease (Hull et al, 2016; Miyamichi et al, 2016), or platelet disorders (Jones et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…With the recent rapid evolution of affordable next‐generation sequencing methods, there is increased recognition of HPS subjects and new HPS genetic subtypes (Arcot Sadagopan et al, 2017; Wei et al, 2016; Yousaf et al, 2016). This is also evidenced by the increased diagnosis of subjects with nonclassic HPS phenotypes (i.e., HPS‐2, HPS‐7, HPS‐8, HPS‐9, and HPS‐10; Ammann et al, 2016; Bryan et al, 2017; Cetica et al, 2015; Iwata et al, 2017; Okamura et al, 2018), as well as diagnosis of “unexpected” HPS in cohorts with albinism (S. Ito et al, 2005; Khan et al, 2016), immunodeficiency (Badolato et al, 2012), ocular disease (Hull et al, 2016; Miyamichi et al, 2016), or platelet disorders (Jones et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in genes encoding these BLOC‐2 subunits are associated with a mild phenotype. In general, mutations affecting the HPS6 gene are rare; only few reports have been published …”
Section: Discussionmentioning
confidence: 99%
“…Oculocutaneous albinism is characterized by diffuse hypopigmentation of the hair, skin, iris, and retina that leads to reduced visual acuity and nystagmus . Mutations present in the OCA1‐4 genes typically impact melanin pigment synthesis in hair, skin, or eye .…”
Section: Introductionmentioning
confidence: 99%
“…One of the study demonstrated HPS6 diagnosis based on foveal hypoplasia, ocular albinism or OCA though they have mild and late systemic manifestations and a diagnosis of HPS [20].…”
Section: Systemic Involvementmentioning
confidence: 99%